Distance Teacher Trainee Perception of Teaching Practice Mentors at the University of Cape Coast, Ghana. - Akuamoah-Boateng, Clara; Sam-Tagoe, Josephine (Advances in Social Sciences Research Journal, 2018)
Mentoring as part of teaching practicum has emerged as an effective process through which the professional competencies of trainee-teachers are developed. The practicum experience of teacher training could be pertinent in the context of distance education where the mode of delivery is mainly by print, which do not allow the modelling of acting out ideal examples of teaching. The role of the mentor teacher in the distance education environments of public universities in Ghana therefore becomes critical in quality teacher development. The placement of teacher mentors in school locations for Distance Education trainee teachers during teaching practice helps trainee teachers to model good teaching skills. Trainee teachers are assisted to plan, teach and reflect on their lesson delivery with the view of improving their professional competencies. This paper examines the perception of Distance Education trainee teachers on teacher mentors placed at their school locations during teaching practice. A structured questionnaire was developed to collect data, which was analysed quantitatively using descriptive statistics. The results of the findings based on support for lesson preparation, teaching skills, coaching, teaching experience, and teacher mentors feedback, indicated that more attention could be focused on improving the mentorship of Distance Education trainee teachers at the University of Cape Coast during teaching practice in order to produce quality teachers for the education sector. It was however recommended that strategies to improve and strengthen the mentoring system at the University of Cape Coast, College of Distance Education be planned well to achieve the expected outcomes to the full benefit of trainee teachers.